2006
DOI: 10.1177/1350507606073424
|View full text |Cite
|
Sign up to set email alerts
|

Who Trusts? Personality, Trust and Knowledge Sharing

Abstract: The strategic importance of knowledge sharing and its relationships with organizational and managerial (i.e. environmental) factors have been well documented. The effects of some context-specific individual factors—including interpersonal trust—on knowledge sharing have also been investigated. The effects of enduring and pervasive individual factors (i.e, personality) on knowledge sharing have not been adequately described empirically. This article links personality, specifically agreeableness, a broad persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
301
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 405 publications
(331 citation statements)
references
References 85 publications
8
301
0
8
Order By: Relevance
“…Cook and Wall (1980:39) conclude that "trust between individuals and groups within organizations is a highly important ingredient in the long-term stability of the organization and the well-being of its members." Studies into the effects of interpersonal trust have found that it helps create more positive attitudes in the workplace, including satisfaction with the job and commitment at work Ferrin, 2001, 2002;Mooradian et al, 2006). Individuals working in an organization where a high level of confidence is present perceive themselves as a valued and important part of the organization, come to work with more enthusiasm, and are happier with their jobs (Altuntas and Baykal, 2009).…”
Section: Insert Figure 1 ------------------------mentioning
confidence: 99%
“…Cook and Wall (1980:39) conclude that "trust between individuals and groups within organizations is a highly important ingredient in the long-term stability of the organization and the well-being of its members." Studies into the effects of interpersonal trust have found that it helps create more positive attitudes in the workplace, including satisfaction with the job and commitment at work Ferrin, 2001, 2002;Mooradian et al, 2006). Individuals working in an organization where a high level of confidence is present perceive themselves as a valued and important part of the organization, come to work with more enthusiasm, and are happier with their jobs (Altuntas and Baykal, 2009).…”
Section: Insert Figure 1 ------------------------mentioning
confidence: 99%
“…Next an eye tracking calibration was done to ensure reasonable precision in tracking eye movements followed by a demographic and skill questionnaire which included questions about the participants' age, gender, major, and educational level. The questionnaire also included five questions measuring interpersonal trust adopted from a questionnaire by Mooradian et al [16]. The questions are shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Future research should examine knowledge sharing from different theoretical perspectives and investigate the potential mechanisms through which knowledge sharing can be fostered. Moreover, future studies using variables of social interdependence theory such as psychological safety (Zhang, Fang, Wei, & Chen, 2010), individuals' characteristics and cultural characteristic (Mooradian, Renzl, & Matzler, 2006;Ardichvili, Maurer, Li, Wentling, & Stuedemann, 2006) may help increase our understanding of the conditions under which knowledge sharing is likely to occur.…”
Section: Future Research Directionsmentioning
confidence: 99%